Development of De Novo Donor-specific HLA Antibodies and AMR in Renal Transplant Patients Depends on CYP3A5 Genotype. Issue 5 (1st July 2021) - Friebus-Kardash, Justa; Nela, Ejona; Möhlendick, Birte; Kribben, Andreas; Siffert, Winfried; Heinemann, Falko Markus; Eisenberger, Ute
Abstract : Background: The single-nucleotide polymorphism CYP3A5 rs776746 is related to a reduction in the metabolizing activity of the CYP3A5 enzyme. People carrying at least one copy of the wild-type allele, defined as CYP3A5 expressers, exhibit higher clearance and lower trough concentrations of tacrolimus than homozygous nonexpressers, and this difference may affect alloimmunization and allograft function. Methods: We retrospectively studied 400 kidney transplant recipients treated with a tacrolimus-based immunosuppression regimen to detect CYP3A5 genotype, de novo formation of HLA antibodies and donor-specific antibodies (DSAs), and clinical outcome up to 5 y after transplant. Results: We found that 69 (17%) of the 400 patients were CYP3A5 expressers. During the first 3 y after transplant, CYP3A5 expressers tended to have lower tacrolimus trough levels than nonexpressers, although their tacrolimus dosage was as much as 80% higher. De novo DSAs were found more frequently in CYP3A5 expressers than in nonexpressers (13/69 [19%] versus 33/331 [10%], P = 0.02). De novo DSA-free survival rates ( P = 0.02) were significantly lower for expressers than for nonexpressers. CYP3A5 genotype had no effect on allograft failure, but CYP3A5 expressers exhibited a significantly higher frequency of antibody-mediated rejection. CYP3A5 expresser status was an independent risk factor for the development of de novo DSAs (relative risk, 2.34, P = 0.01). Conclusions: Early detection of CYP3A5 expressers, enabling genotype-based dose adjustment of tacrolimus immediately after renal transplant, may be a useful strategy for reducing the risk of de novo DSA production and antibody-mediated rejection.